Optimization of Tourism Experiences to Enhance Revisit Intention: Analysis of Destination Image and Accessibility in Yogyakarta - Vely Randyantini; Ika Puji Saputri; Ari Apriani; Siti Annisa Wahdiniawati (Universitas Mercu Buana, 2026)
Despite extensive research on revisit intention, limited studies have integrated accessibility, destination image, and memorable tourism experiences within a unified predictive framework that explicitly examines tourist satisfaction as a mediating mechanism, particularly in cultural tourism destinations. Addressing this gap, this study investigates the direct and indirect effects of Accessibility, Destination Image, and Memorable Tourism Experiences on Revisit Intention, with Satisfaction positioned as a mediating variable, in the context of Yogyakarta, Indonesia. A quantitative survey was conducted involving 195 domestic tourists who had visited Yogyakarta within the last six months. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships and mediation effects. The results indicate that Memorable Tourism Experiences exert the strongest effect on Satisfaction (β = highest among predictors) and have a significant direct impact on Revisit Intention. Accessibility and Destination Image also significantly enhance Satisfaction, which in turn demonstrates a strong positive influence on Revisit Intention. Mediation analysis confirms that Satisfaction significantly mediates the effects of Accessibility, Destination Image, and Memorable Tourism Experiences on Revisit Intention, highlighting its central role in shaping repeat-visit behavior. This study contributes theoretically by extending the revisit intention literature through an integrated mediation-based model that clarifies the psychological mechanism linking destination attributes to behavioral intention in cultural tourism contexts. From a managerial perspective, the findings underscore the importance of prioritizing experience design, improving destination accessibility, and maintaining a consistent destination image as strategic levers to enhance tourist loyalty and sustainable destination competitiveness.